Hubungan Motivasi Berprestasi Minat dan Perhatian Orang Tua Terhadap Hasil Belajar Kognitif Biologi Siswa SMA Negeri Se-Kecamatan Medan Kota - Intan Bayati Nasution; Hasruddin Hasruddin; Syahmi Edi (Magister Pendidikan Biologi, Universitas Negeri Medan, 2016)
This study aims to determine the relationships between: (1) Achievement motivation; (2) Interest; (3) Carefullness of parents toward biology cognitive learning outcome; (4) Achievement motivation and interest; (5) Achievement motivation and carefullness of parents; (6) Interest and carefullness of parents together on biology cognitive learning outcome. This study was conducted at SMA Sekecamatan Medan Kota. The study method using is correlational descriptive with study sample as much as 275 students’ who are by purposive sampling that’s are SMA Negeri 5 as much as 138 students’, SMA Negeri 6 as much as 65 students’, and SMA Negeri 10 as much as 72 students’. The study instrument using questionnaire of achievement motivation with total 30 statement, questionnaire of interest with total 20 statement, questionnaire of carefullness of parents with total 25 statement, whereas value of biology cognitive learning outcome resulted from biology result semester I which there are in each school. Analysis techniques used is correlation with the help program SPSS 21.0 for windows. The stuy result shows that there are significant relationship between: (1) Achievement motivation toward biology cognitive learning outcome (r=0,536 ; p=0,000); (2) Interest toward biology cognitive learning outcome (r=0,482 ; p=0,000); (3) Carefullness of parents toward biology cognitive learning outcome (r=0,250 ; p=0,000); (4) Achievement motivation and interest together on biology cognitive learning outcome (r=0,603 ; p=0,000); (5) Achievement motivation and carefullness of parents together on biology cognitive learning outcome (r=0,546 ; p=0,000); (6) Interest and carefullness of parents together on biology cognitive learning outcome (r=0,499 ; p=0,000).